Perencanaan Sumber Daya Manusia: Kunci Keberhasilan Pendidikan Abad ke-21 - Zohriah, Anis; N.B, Muh. Shofwan Mawally; Mu'in, Abdul (EduInovasi: Journal of Basic Educational Studies, 2024)
Human Resource Planning (HRP) in the context of 21st century education is the key to the success of educational institutions. The global transformation that is taking place in this era demands the adaptation of the education system to meet the increasingly complex and dynamic needs of society. This research aims to investigate the role of HRP in supporting the success of 21st century education. The research methodology involves literature analysis and case studies of HRP implementation in several leading educational institutions. The results of the research show that effective HRP requires strategic integration between government policies, educational institution management, and teacher empowerment. Curriculum renewal, training for teachers in using cutting-edge technology, and the application of innovative teaching methods are critical elements in successful HRP.